Diseño y construcción de un prototipo de generación eléctrica a partir de una bicicleta estática - Caraguay Pauta, Henry Javier (2024)
This project focuses on designing a prototype to harness the residual energy from the flywheel of stationary bicycles, utilizing the human body's propulsive capacity. The main and set objectives, were achieved by starting with the selection of a suitable power transmission system, employing the roller chain method, known for its efficiency in transporting mechanical power. On the other hand, the material selection was focused on avoiding bulkiness to prevent hindrance to physical activity on the stationary bicycle. The 350 W DC generator was attached to the stationary bicycle's structure using 1 1/2 in U-type clamps. Additionally, connection diagrams were created to illustrate the arrangement of electronic components. Performance testing of the constructed prototype was carried out with an experimental group, aged between 23 and 35 years. The obtained parameters were voltage at 13.51 V, current at 4.33 A, and generated power at 58.43 W critical data for determining the prototype's efficiency, yielding a value of 13%. This is considered acceptable, according to Reyes (2021), when comparing it to the efficiency of a silicon photovoltaic cell, which ranges between 4% and 17%, accounting for losses due to friction and various electrical factors. The implemented system defines the electrical generation parameters of the prototype, capable of meeting energy demands. Consequently, a technical data sheet was developed to highlight relevant generation system parameters. Unit cost analysis of the equipment was performed to estimate the budget for the electrical generation system's implementation, revealing a return on investment time of 10 years, rendering the project financially unviable. Keywords: stationary bicycle, residual energy, renewable energy, DC generator, current, electrical power.